Institute of Philosophy of St. Petersburg State University: Pages of History - S. I. Dudnik (Высшее образование в России)
The article presents a philosophical analysis of the history of the Faculty of Philosophy, starting with Peter the Great’s reforms and ending with its modern state. It is believed that the University of St. Petersburg was organized on the basis of a note by Leibniz to Peter the Great. In fact, there is no direct coincidence, since the university was built and developed in accordance with the capabilities and needs of the Russian Empire. Even at first, the first teachers were not Germans, but the so-called “Rusyns” (Leibniz also had Slavic roots). The example of the professors’ biographies revealed little-known pages of the history of Russian philosophy. Particular attention is paid to the search for a model of philosophical education in the post-revolutionary time. In accordance with the doctrine of the three constituent parts of Marxism, the emphasis was first placed on ideology and dialectic. Then philosophy was used in the struggle for “proletarian science.” In the 60s it gained relative independence, promoted the development of the theory of cognition, sociology and theory of values. The “golden age” of Russian philosophy began in the 90-s thanks to the talented workers of the Faculty of Philosophy, who published many original works that had a significant impact on the worldview of society. The accelerated development of scientific and educational activities has been made possible by adequate structural changes in the institutions of humanities education. The experience of its reforming is also useful in today’s environment.